MAUDUâ€™ (A WAY OF UNION WITH GOD) - Rita Sukma Dewi (Balai Penelitian dan Pengembangan Agama Jakarta, 2018)
The term â€œSayyidâ€ or â€œArabâ€ has always been associated with Islam in Indonesia. Since Islam originated in the land of Arab, Muslims in Indonesia often believe that religion and Arab race are similar, just as the term â€œCultureâ€ or â€œReligionâ€, although they have different context, many people believe that the term â€œcultureâ€ is similar to â€œreligionâ€. Religious influences are embedded in many aspects of culture but Arabic culture is not an identity about Islam, these two should be separate from one another.